Peningkatan Nafkah Anak Pasca Perceraian dalam Pasal 14 Surat Edaran Mahkamah Agung Nomor 3 Tahun 2015 Ditinjau dari Fiqh Madzhab Syafi'i: (Analisis Putusan Pengadilan Agama Mojokerto Nomor Perkara 1835/Pdt.G/2023/PA.Mr) - Berliana Aliefia Putri; Fatkul Chodir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The results of this research are: Judging from the Syafi'i madzhab fiqh related to the contents of the decision in case Number 1835/Pdt.G/2023/PA.Mr which includes child support and implementing the policy in article 14 of the Supreme Court Circular Letter Number 3 of 2015 regarding increases child support is 10% per year of the specified amount excluding education and health costs, which is not in accordance with the theory of fiqh of the Syafi'i school of thought. In the Syafi'i school of fiqh there is no special provision that regulates the increase in the amount of child support by 10% every year after divorce. The child support decision in case Number 1835/Pdt.G/2023/PA.Mr, which experienced an increase of 10% per year in long-term calculations, is increasingly increasing and making it difficult for the father's economy to meet the child's support demands.